ALSUntangled #64: butyrates. Issue 7 (2nd October 2022) - Sun, Yuyao; Bedlack, Richard; Armon, Carmel; Beauchamp, Morgan; Bertorini, Tulio; Bowser, Robert; Bromberg, Mark; Caress, James; Carter, Gregory; Crayle, Jesse; Cudkowicz, Merit E.; Glass, Jonathan D.; et al.
Abstract: ALSUntangled reviews alternative and off-label treatments for people living with amyotrophic lateral sclerosis (PALS). Here we review butyrate and its different chemical forms (butyrates). Butyrates have plausible mechanisms for slowing ALS progression and positive pre-clinical studies. One trial suggests that sodium phenylbutyrate (NaPB) in combination with Tauroursodeoxycholic acid (TUDCA) can slow ALS progression and prolong survival, but the specific contribution of NaPB toward this effect is unclear. Butyrates appear reasonably safe for use in humans. Based on the above information, we support a trial of a butyrate in PALS, but we cannot yet recommend one as a treatment.